Orientação farmacêutica de idosos com hipertensão arterial em acompanhamento no ambulatório da geriatria e gerontologia da UNIFESP - Moura, Beatriz Vieira de [UNIFESP] (2018)
Introduction: the aging of the Brazilian population progressively changes the profile of the Brazilian population, changing the epidemiological characteristics evidencing a higher incidence of chronic diseases, such as hypertension associated with more than one comorbidity. It should be emphasized that in Brazil the frequency of systemic arterial hypertension (SAH) affects more than 50% of the population aged 65 years or more. Such conditions frequently require the use of polymediction, which in turn can lead to nonadherence to treatment and problems related to medications. The pharmaceutical orientation is shown as an important tool as a process for the education of hypertensive patients, aiming at adherence to treatment and optimization of pharmacotherapeutic results in the search to reduce drugrelated problems (DRP). Objective: to analyze the effectiveness of pharmaceutical orientation in the elderly with hypertension in the improvement of therapeutic adherence and in the control of blood pressure. Methods: This is study it is a randomized clinical trial design. Results: The presence of polypharmacy and PRM was observed in the study and the educational intervention improved the knowledge of the elderly of the study in relation to the disease.